Dystocia due to feto-pelvic disproportion in a squirrel monkey - HONPARKHE, M; KUMAR, AJEET; GHUMAN, S P S; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
A rare case of dystocia in a captive squirrel monkey relieved by obstetrical manoeuvering is documented.